A Systematic Review of Non-Invasive Brain Stimulation Therapies and Cardiovascular Risk: Implications for the Treatment of Major Depressive Disorder - Sampaio, Leonardo A.; Fraguas, Renerio; Lotufo, Paulo; Benseñor, Isabela; Brunoni, Andre R. (Frontiers in Psychiatry, 2012)
Major depressive disorder (MDD) and cardiovascular diseases are intimately associated. Depression is an independent risk factor for mortality in cardiovascular samples. Neuroendocrine dysfunctions in MDD are related to an overactive hypothalamus-pituitary-adrenal (HPA) axis and increased sympathetic activity. Novel intervention strategies for MDD include the non-invasive brain stimulation (NIBS) techniques such as repetitive transcranial magnetic stimulation (rTMS) and transcranial direct current stimulation (tDCS). In fact, although these techniques have being increasingly used as a treatment for MDD, their cardiovascular effects were not sufficiently investigated, which would be important considering the dyad MDD/cardiovascular disorders. We investigated this issue through a systematic review for published articles from the first date available to May 2012 in MEDLINE and other databases, looking for main risk factors and surrogate markers for cardiovascular disease such as: cortisol, heart rate variability, alcohol, smoking, obesity, hypertension, glucose. We identified 37 articles (981 subjects) according to our eligibility criteria. Our main findings were that NIBS techniques might be effective strategies for down-regulating HPA activity and regulating food, alcohol and cigarette consumption. NIBS’s effects on HRV and blood pressure presented mixed findings, with studies suggesting that HRV values can decrease or remain unchanged after NIBS, while one study found that rTMS increased blood pressure levels. Also, a single study showed that glucose levels decrease after tDCS. However, most studies tested the acute effects after one single session of rTMS/tDCS; therefore further studies are necessary to investigate whether NIBS modifies cardiovascular risk factors in the long-term. In fact, considering the burden of cardiac disease, further trials in cardiovascular, depressed and nondepressed samples using NIBS should be performed.